Why the standard TFR gives a misleading impression of the fertility of foreign women: Insights from Switzerland - Marion Burkimsher; Clémentine Rossier; Philippe Wanner (Comparative Population Studies (CPoS), 2020)
Since 1971 the Swiss Federal Statistical Office has published annual fertility data split by nationality (Swiss/foreign). These indicate that the TFR for women of foreign nationality has been 0.5 children higher than for Swiss women for most of the period since 1991. However, statistics from household registration (STATPOP) and the Families and Generations Surveys (FGS) in 2013 and 2018 indicate that foreign women, approaching the end of their reproductive lives, have slightly smaller families than women of Swiss nationality. The purpose of this paper is to reconcile these contradictory fertility measures. To do this, we design a novel methodology for tallying the fertility of cohorts of Swiss and foreign nationals through their reproductive life. In addition to birth registrations and population totals by age (the input data for calculating the TFR) we also include estimates of how many children women have at the time of their immigration, emigration and naturalisation. Using these input data, we compile the fertility profiles of Swiss and foreign women aged 15-49 (cohorts 1966-2003). These correspond well with the FGS and household register data. Several processes impact the final fertility of the two sub-populations. Women frequently immigrate into Switzerland in their 20s. Often arriving childless, they commonly start childbearing soon after immigration. However, there is still a flow of low-fertility women into the country in their 30s and 40s, lowering the average fertility of the foreign population. By contrast, Swiss women start childbearing later and a significant proportion remain childless; however, after starting childbearing they have a higher propensity than foreign women to have a second and third child. Naturalisation and fertility are interlinked; women with children are more likely to naturalise than those without, which then boosts the average fertility of the Swiss population. We confirm that the standard TFR gives an inflated impression of the ultimate (cohort) fertility of foreign nationals and under-estimates that of Swiss women, and we describe how this happens. Fundamentally, the TFR is a measure of childbearing intensity, not an accurate estimate of completed cohort fertility, especially for a mobile population.
urn:nbn:de:bib-cpos-2020-23en6
Keywords: 300; Immigrant fertility; Fertility of foreigners; TFR; Cohort fertility; Immigration; Timing of childbearing; Naturalisation; Postponement